Impacts of relay and direct links at destinations in full-duplex non-orthogonal multiple access system - Dinh-Thuan Do; Tu-Trinh Thi Nguyen (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
In this study, one of effective methods of multiple access, namely non-orthogonal multiple access (NOMA), is investigated. Such NOMA scheme can be worked with signal processing at downlink side. As such, the base station sends mixed signals of two signals to destinations. A near user could be a relay to forward the signal to the distant user by leveraging benefits of full-duplex mode which allows relay to transmit and receive signals in the same time. For simple analysis, the two-user approach and fixed power allocation factors are implemented. We also derive formulas of the outage probability of two users (near-user and far-user) to indicate fairness and emphasize the role of the near user as a relay. This considered NOMA system adopts transmission with Nakagami-m fading channel. As a further metric, throughput is considered under the impacts of key system parameters. The transmit signal-to-noise ratio (SNR) at the base station make influences the performance of two users significantly as observation indicated in our simulation results. These results are confirmed by matching Monte-Carlo with the theoretical simulations.